2000
DOI: 10.1073/pnas.97.13.7458
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CD40 signaling limits evolution of established atherosclerosis in mice

Abstract: Interruption of inflammatory pathways may provide a novel approach to the therapy of atherosclerosis. Recently, we and others have implicated the immune mediator dyad CD40͞CD40L (CD40 ligand), which is expressed on endothelial and smooth muscle cells, macrophages, and T lymphocytes within human atherosclerotic lesions, in aspects of atherogenesis and the acute coronary syndromes, including regulation of matrix metalloproteinases, procoagulant activity, cytokines, etc. In vivo, interruption of CD40 signaling re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
228
2
5

Year Published

2001
2001
2009
2009

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(238 citation statements)
references
References 58 publications
3
228
2
5
Order By: Relevance
“…It is now established that this pathway, in addition to playing an essential role in cellular immunity as traditionally acknowledged, is a key component of the pathophysiology of multiple inflammatory disorders, including vascular inflammation (14, 43, 44), which is dependent on the integrated signaling pathways of CD40 and TNF-␣. This integration has been confirmed in murine models, where inhibition of CD40 signaling decreases inflammatory infiltrates in established atherosclerotic lesions (45) and TNF-␣ blockade reduces progression of atherosclerosis (46). A recent but growing body of evidence indicates that vascular inflammation is also an important component of IBD pathogenesis (47).…”
Section: Discussionmentioning
confidence: 66%
“…It is now established that this pathway, in addition to playing an essential role in cellular immunity as traditionally acknowledged, is a key component of the pathophysiology of multiple inflammatory disorders, including vascular inflammation (14, 43, 44), which is dependent on the integrated signaling pathways of CD40 and TNF-␣. This integration has been confirmed in murine models, where inhibition of CD40 signaling decreases inflammatory infiltrates in established atherosclerotic lesions (45) and TNF-␣ blockade reduces progression of atherosclerosis (46). A recent but growing body of evidence indicates that vascular inflammation is also an important component of IBD pathogenesis (47).…”
Section: Discussionmentioning
confidence: 66%
“…These include TXA2, a costimulator of platelets that has vasoconstrictive activity; P-selectin, an ␣-granule protein that mediates platelet rolling, leukocyte adhesion, and coagulation; ADP and serotonin, which amplify platelet aggregation; platelet-derived growth factor, a growth factor for vascular cells; and CD40L, a member of the tumor necrosis factor-␣ family of proteins (reviewed in Gresele et al 4 ). Although any of these factors could contribute to long-term vascular pathologies, CD40L appears to be particularly relevant because this protein is now known to be prothrombotic 5 and proinflammatory, to have a proven role in atherosclerotic lesion progression, 6 and to be a risk factor for cardiovascular events. 7 CD40 ligand (CD40L, CD154, gp39) was originally identified in T lymphocytes, where it has a role in the immune response by binding to its receptor on B cells, CD40 (reviewed in Schonbeck and Libby 8 ).…”
mentioning
confidence: 99%
“…In situ analysis of human atherosclerotic lesions revealed the co-expression of CD154 and CD40 on vascular endothelium and smooth muscle cells (15). Blockade of CD40-CD154 interaction in atherosclerosis was found not only to diminish the formation and progression of mouse atheroma but also to foster changes in lesions associated with plaque destabilization (16,17). Recently, it has also been shown that the engagement of CD40 on endothelial cells by CD154 induces in vitro vessel-like tubule formation and expression of matrix metalloproteinases, two events involved in neovascularization (18).…”
mentioning
confidence: 99%